TINJAUAN LITERATUR TENTANG TANTANGAN DAN PELUANG PROFESI GURU DI ERA DIGITAL - Annisa Nur Azizah; Salma Azizah Azzahra; Annisa Wulandari; Ratri Dian Aprilia; Safira Nur Sabillah (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2024)
The digital era provides significant challenges for the teaching profession, especially in the face of rapid technological developments. Teachers are required to be able to adapt to technology and utilize it in learning. The success of teachers in mastering technology is the main key in facing the digital era. One of the major challenges is the gap in access to technology that exists in various regions. Another challenge is the rapid changes in curriculum and assessment. The research method used in this article is the literature review method, where data is obtained from various secondary sources such as scientific journals, books, and related articles relevant to the topic of opportunities and challenges of the teaching profession in the digital era. The data is analyzed by reading, sorting and interpreting information from these sources to find patterns, trends and key challenges faced by teachers, and then organized systematically to provide a comprehensive picture of the issues discussed. This includes not only mastery of subject matter, but also skills in using technological tools that support the teaching and learning process. In the digital era, an outdated curriculum is no longer relevant to the needs and development of technology. Another opportunity is the development of multicultural teaching materials. the digital era also provides an opportunity for teachers to introduce ecological intelligence to students.